Lacticaseibacillus paracasei HP7 Attenuates Helicobacter pylori Activity and Improves Upper Gastrointestinal Symptoms: A Double-Blind, Randomized, Placebo-Controlled, Clinical Trial - Jae-Ho Lee; Ju-Yeon Kim; Eun-Ji Kim; Il-Dong Choi; Jae-Jung Shim; Seong-Soo Hong; Jong-Cheon Joo; Jae-Hwan Lee (Journal of Medicinal Food, 2026)
Helicobacter pylori remains a major cause of chronic gastritis and dyspeptic symptoms, and the effectiveness of standard eradication therapy continues to decline with increasing antibiotic resistance. Lacticaseibacillus paracasei HP7 has shown inhibitory and anti-inflammatory effects on H. pylori in preclinical studies. This study investigated whether 8-week oral HP7 supplementation could improve H. pylori -related outcomes in adults with confirmed infection. Seventy-eight adults with positive 13 C-urea breath test ( 13 C-UBT) results and gastric discomfort were randomized to receive low-dose HP7 (HP7-L, 1.5 × 10 9 CFU/day), high-dose HP7 (HP7-H, 5.0 × 10 9 CFU/day), or placebo for 8 weeks. Outcomes included changes in 13 C-UBT values, upper gastrointestinal (GI) symptoms assessed by Korean Gastrointestinal Symptom Rating Scale, pepsinogen I/II ratio, serum tumor necrosis factor-α, and quality-of-life indices. HP7-H significantly reduced 13 C-UBT values compared with placebo. HP7 supplementation was also associated with improvements in gastric mucosal biomarkers and modest changes in selected upper GI symptom and quality-of-life domains. Overall microbial diversity was not significantly altered, although the abundance of L. paracasei increased following supplementation. No treatment-related serious adverse events were observed, and all laboratory findings remained within clinical reference ranges. Complete eradication of H. pylori was not achieved in most participants. These findings support the clinical potential of HP7 supplementation to attenuate H. pylori -related activity and improve gastric biomarkers, with modest benefits in selected dyspeptic symptom domains. HP7 may be a safe and effective functional food option for H. pylori management when antibiotics are contraindicated or ineffective. Further studies are warranted to confirm long-term efficacy and durability of these effects.